National Legal Reforms about Unofficial Marriage (Jurnal Cita Hukum, 2017)
The legal consequences of Constitutional Court Decision Number 46/PUU-VIII/2010 perspective of national law reform are a progressive development of the law. The ruling granted part of the petition for judicial review of Article 2 (2) and Article 43 (1) of Law Number 1 in 1974 concerning Procurement of Articles 28B (1) and (2), and Article 28 D (1) of the 1945 Constitution of the Republic of Indonesia. The review of Article 2 (2) of the Marriage Law is not granted because the Constitutional Court is of the opinion that marriage registration is not a marriage restriction, but an orderly form of administration. Material review Article 43 (1) of the Marriage Law is granted by the Constitutional Court so that the child is a legal child. The Constitutional Court's decision on the unofficial marriage has positive and negative implications. One of the positive implications is the recognition of the child's relationship status with his biological father as long as it can prove the relationship and have a negative impact because it creates a sense of calm for the offender unofficial marriage (nikah sirri) and increase the quantity.  Akibat hukum putusan MK No.46/PUU-VIII/2010 perspektif pembaharuan hukum nasional merupakan pembangunan hukum progresif. Putusan tersebut mengabulkan sebagian permohonan pengujian materiil pasal 2 (2) dan pasal 43 (1) UUP terhadap pasal 28B (1) dan (2), serta  pasal 28D (1) UUD NRI tahun 1945. Pengujian materiil pasal 2 (2) UUP tidak dikabulkan karena Mahkamah Konstitusi berpendapat pencatatan perkawinan bukan pembatasan perkawinan, melainkan bentuk tertib administrasi. Pengujian materiil pasal 43 (1) UUP dikabulkan MK, sehingga anak tersebut berstatus  anak sah. Fenomena nikah sirri menurut penulis, putusan MK mempunyai implikasi positif dan negatif. Berdampak positif adanya pengakuan status hubungan anak dengan ayah biologisnya sepanjang dapat membuktikan hubungan tersebut dan berdampak negatif karena menimbulkan rasa tenang bagi pelaku nikah sirri dan bertambah kuantitasnya. DOI: 10.15408/jch.v5i1.4691